2011
DOI: 10.1001/archoto.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy for Advanced Squamous Cell Carcinoma of the Paranasal Sinuses

Abstract: Tumor response to induction chemotherapy in patients with advanced squamous cell carcinoma of the paranasal sinuses may be predictive of treatment outcome and prognosis. Favorable response to induction chemotherapy is associated with better survival and a reasonable chance of organ preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 18 publications
5
115
2
1
Order By: Relevance
“…Hanna et al reported on a retrospective series of 46 patients with previously untreated biopsy-proven SCC of the paranasal sinuses treated with induction chemotherapy at the MD Anderson Cancer Center (MDACC) in the US [29]. Eighty percent of patients had stage IV disease, 67% had orbital invasion and 26% had nodal metastases.…”
Section: Neoadjuvant (Induction) Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Hanna et al reported on a retrospective series of 46 patients with previously untreated biopsy-proven SCC of the paranasal sinuses treated with induction chemotherapy at the MD Anderson Cancer Center (MDACC) in the US [29]. Eighty percent of patients had stage IV disease, 67% had orbital invasion and 26% had nodal metastases.…”
Section: Neoadjuvant (Induction) Chemotherapymentioning
confidence: 99%
“…The choice of the type of chemotherapy according to histologically defined tumor type has not been specifically addressed in the reported trials. However, most of the previously reported studies employed platinum-based chemotherapy in combination with either 5-fluorouracil, taxane, ifosfamide, or vincristine [25][26][27][28][29].…”
Section: Neoadjuvant (Induction) Chemotherapymentioning
confidence: 99%
“…outcomes for patients with SCC of the paranasal sinuses [11], and NAC followed by CRT is also considered to be an option for locally advanced NC&ES.…”
Section: Hanna Et Al Reported That Nac Is a Promising Technique Thatmentioning
confidence: 99%
“…Generally, these reports contain small numbers of patients with relatively short follow-ups. 13 For esthesioneuroblastoma, local recurrences can develop 10 years or more after the completion of treatment, so prolonged follow-up is needed. With surgical techniques changing rapidly, craniofacial resection remains an important standard by which other treatments for esthesioneuroblastoma should be judged.…”
Section: Surgery In the Management Of Sinonasal Cancermentioning
confidence: 99%
“…Long-term outcomes and toxicity results are still pending. 13 Although chemosensitivity may identify patients with a better prognosis, it is unlikely that patients who progressed during chemotherapy benefited from the delay in definitive local treatment. The role of induction chemotherapy in the setting of paranasal sinus cancer remains under investigation.…”
Section: Nonsurgical Management Of Sinonasal Malignanciesmentioning
confidence: 99%